Обоснование требований к построению импульсного генератора для коррекции иммунного дефицита у новорождённых животных - Торчук, Михаил Васильевич (НТУ "ХПИ", 2014)
Рассмотрены принципы построения импульсного генератора и приведены функциональные, структурные и электрические принципиальные схемы элементов и узлов генератора.

The paper considers principles of construction of the pulse generator and gives functional, structural and electrical schematic diagrams of elementsand components of the generator.
Validation of requirements to construction of pulse generator for correction of immunodeficiency in newborn animals
Keywords: устройство синхронизирующих импульсов; магнитный накопитель энергии; токовый ключ; animal immune deficiency; synchronization pulse device; current switch